A Comprehensive Analysis of Fibroblast Growth Factor Receptor 2b Signaling on Epithelial Tip Progenitor Cells During Early Mouse Lung Branching Morphogenesis - Jones, Matthew R.; Dilai, Salma; Lingampally, Arun; Chao, Cho-Ming; Danopoulos, Soula; Carraro, Gianni; Mukhametshina, Regina; Wilhelm, Jochen; Baumgart-Vogt, Eveline; Al Alam, Denise; Chen, Chengshui; Minoo, Parviz; et al. (Frontiers in Genetics, 2019)
Fibroblast growth factor (FGF) 10 signalling through FGF receptor 2b (FGFR2b) is mandatory during early lung development as the deletion of either the ligand or the receptor leads to lung agenesis. However, this drastic phenotype previously hampered characterization of the primary biological activities, immediate downstream targets and mechanisms of action. Through the use of a dominant negative transgenic mouse model (Rosa26rtTA; tet(o)sFgfr2b), we conditionally inhibited FGF10 signalling in vivo in E12.5 embryonic lungs via doxycycline IP injection to pregnant females, and in vitro by culturing control and experimental lungs with doxycycline. The impact on branching morphogenesis 9 hours after doxycycline administration was analyzed by morphometry, fluorescence and electron microscopy. Gene arrays at 6 and 9 hours following doxycycline administration were carried out. The relationship between FGF10 and ß-catenin signalling was also analyzed through in vitro experiments using IQ1, a pharmacological inhibitor of ß-catenin/EP300 transcriptional activity. Loss of FGF10 signalling did not impact proliferation or survival, but affected both adherens junctions (up-regulation of E-cadherin), and basement membrane organization (increased laminin). Gene arrays identified multiple direct targets of FGF10, including main transcription factors. Immunofluorescence showed a down-regulation of the distal epithelial marker SOX9 and mis-expression distally of the proximal marker SOX2. Staining for the transcriptionally-active form of ß-catenin showed a reduction in experimental versus control lungs. In vitro experiments using IQ1 phenocopied the impacts of blocking FGF10. This study demonstrates that FGF10/FGFR2b signalling on distal epithelial progenitor cells via ß-catenin/EP300 controls, through a comprehensive set of developmental genes, cell adhesion and differentiation.